PHYSIOLOGY CHARACTERISTICS OF MANGOSTEEN (Garcinia Mangostana L.) AT MODIFIED ATMOSPHERE CONDITION - Agustina, Nanik; Waluyo, Sri; -, Warji; -, Tamrin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
The entry of water into seed until reached saturation point on the soaking process at room temperature, in common, may take more than one day. Mean while, longer soaking time can cause microbial contamination and may influence product quality in term of color, taste, and smell. Soaking in warmer liquid method is a common method used for shortening the soaking time. The objective of this research was to determine the effect of soaking temperature on the coefficient of diffusion and on the physical properties of Kidney bean (Phaseolus vulgaris L.). The research was conducted at 5 different soaking temperatures: 28 oC (control), 35 oC, 40 oC, 45 oC, and 50 oC, with 3 replications for each treatment. The parameters measured were dimensions of specimen, weight of specimen during soaking. The diffusivity of water were than derived from water content data. The results showed that the higher the soaking temperature, the faster the change of dimensions, weight, and water content. The coefficient of water diffusion of kidney bean at soaking temperatures: 28 oC, 35 oC, 40 oC, 45 oC, and 50 oC, was 12,91 x 10-11 m2/s; 6,42 x 10-11 m2/s; 25,64 x 10-11 m2/s; 60,20 x 10-11 m2/s and 48,24 x 10-11 m2/s, respectively.Â  It showed that the higher temperature, the faster the water diffusion rate and it follows exponential equation with the coefficient of determination, R2 = 0,643. Keywords: Kidney bean, soaking temperature, coefficient of water diffusion, physical properties